2021
DOI: 10.35760/psi.2021.v14i2.4646
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Quarter-Life Crisis Dan Subjective Well-Being Pada Individu Dewasa Muda

Abstract: Masa dewasa muda ditandai dengan adanya tugas perkembangan untuk mulai mengambil peran dan tanggung jawab sebagai individu yang produktif dalam bidang pekerjaan dan karir, relasi, dan finansial. Pada masa ini, individu dewasa muda mengalami berbagai tantangan dan kesulitan yang dapat memunculkan emosi negatif yang nyata dan sering disebut sebagai quarter-life crisis. Di sisi lain, produktivitas individu juga dipengaruhi oleh tingkat well-being individu. Penelitian ini bertujuan untuk mengetahui hubungan antara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This scale used a 5-point Likert scale ranging from 1 (very rarely or never) to 5 (very often or always). Previous studies confirmed that the Indonesian version of SPANE has a favorable internal consistency for SPANE-P and SPANE-N (Novanto & Pali, 2019;Suyono et al, 2021). In this study, SPANE obtained an internal consistency value of .85 for SPANE-P and .79 for SPANE-N. Suyono et al (2021) also conducted CFA, and the results ensure the construct validity of SPANE.…”
Section: Instrumentssupporting
confidence: 80%
See 2 more Smart Citations
“…This scale used a 5-point Likert scale ranging from 1 (very rarely or never) to 5 (very often or always). Previous studies confirmed that the Indonesian version of SPANE has a favorable internal consistency for SPANE-P and SPANE-N (Novanto & Pali, 2019;Suyono et al, 2021). In this study, SPANE obtained an internal consistency value of .85 for SPANE-P and .79 for SPANE-N. Suyono et al (2021) also conducted CFA, and the results ensure the construct validity of SPANE.…”
Section: Instrumentssupporting
confidence: 80%
“…The Indonesian version of SWLS consists of five items using a 7-point Likert scale ranging from 1 ( strongly disagree ) to 7 ( strongly agree ) (Novanto & Pali, 2019). Previous studies reported that the Indonesian version of SWLS has a favorable internal consistency with Cronbach’s alpha ranges between .80 and .83 (Novanto & Pali, 2019; Suyono et al, 2021). SWLS internal consistency in this study yielded .80.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entering the phase of emerging adulthood, a person will experience various psychological problems, feel uncertain in life, and have an emotional crisis commonly known as a quarter-life crisis (Robbins & Wilner, 2001). The quarter-life crisis phase is characterized by helplessness, doubt, ignorance of something, and fear of the future related to career, finances, relationships, and others that occur when a person enters adulthood (Suyono et al, 2021). The quarter-life crisis phase is experienced by a person when they feel trapped by their routine, and it can cause hopelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Menorut (Santrock, 2012) early adulthood is in the age range of 20-30 years. This stage of development often experiences crisis problems which are often referred to as quarter life crises, this is based on previous research that examines the issue of QLS in early adulthood (Putri et al, 2022;Qolbi & Musthofa, 2020;Robinson & Smith, 2010;Suyono et al, 2021;Yeler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%